Sound Learning Strategies for Phase F Students with Intellectual Disabilities in Special Needs Schools - Audina Setyawaty D. Buta; Masri Kudrat Umar; Dewa Gede Eka Setiawan (Universitas Muhammadiyah Palu, 2025)
This study aimed to describe the implementation of physics learning on the sound topic for intellectually disabled students in phase F at Special Schools, and to find out how teachers adjusted strategies, interactions, and learning media based on students’ characteristics. This research used a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, with validation using method triangulation. The results showed that physics learning on the sound topic was conducted in three stages: preliminary, core, and closing activities. In the preliminary stage, the teacher greeted, prayed, and gave appreciation, but the learning objectives were not clearly stated. In the core activities, the teacher used the lecture method with textbooks as the main learning resource, while the use of concrete media or technology was minimal. The interaction between teachers and students tended to be one-way, and not all students were actively engaged.In the closing stage, the teacher asked students to independently summarize the material and assigned homework as an evaluation tool. The learning strategies were mostly verbal and had not fully involved multisensory media or individual approaches tailored to students’ needs.In conclusion, the teacher made efforts to adjust the learning strategies to the characteristics of intellectually disabled students in phase F. However, improvement was still needed, particularly in the use of varied learning media, fostering more active interactions, and applying more concrete and participatory learning approaches to enhance learning effectiveness.